Optic nerve‐associated connective tissue structures revisited: A histological study using human fetuses and adult cadavers. Issue 12 (10th April 2022) - Cho, Kwang Ho; Takahashi, Akihiro; Yamamoto, Masahito; Hirouchi, Hidetomo; Taniguchi, Shuichiro; Ogawa, Yudai; Murakami, Gen; Abe, Shin‐Ichi
Abstract: Unlike the usual peripheral nerve, the optic nerve accompanies a thick "dural sheath, " a thin "sheath of pia mater" (SPM), and multiple "septa, " which divides the nerve fibers into fascicles. We collected specimens from 25 adult cadavers and 15 fetuses and revisited the histological architecture of the optic and oculomotor nerves. In the optic chiasma, the meningeal layer of the dura joins the pia to form a thick SPM, and the periosteum of the sphenoid is continuous with the dural sheath at the orbital exit of the bony optic canal. The septa appeared as a cluster of irregularly arrayed fibrous plates in the intracranial course near the chiasma. Thus, the septa were not derived from either the SPM or the dural sheath. In the orbit, the central artery of the retina accompanies collagenous fibers from the dural sheath and the SPM to provide the vascular sheath in the optic nerve. These connective tissue configurations were the same between adult and fetal specimens. At the optic disk, the dural sheath and SPM merged with the sclera, whereas the septa appeared to end at the lamina cribrosa. However, in fetuses without lamina cribrosa, the septa extend into the nerve fiber layer of the retina. The SPM and septa showed strong elastin immunoreactivity, in contrast to the absence of reactivity in the sheaths of the oculomotor nerve. Each S100 protein‐positive Schwann sheath of the oculomotor nerve was surrounded by collagenous endoneurium. Glial fibrillary acidic protein‐positive astrocytes showed a linear arrangement along the septa.